A Political Reading of Seyyed Mahdi Shojaee's Democracy or DemoCrazy in the light of the Theory of Organizational Structure - Nasrin Fallah (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Organizational structure creates a model for relations among different roles in each organization. It consists of several dimensions, four of which, that is, task division, specialization, focus and control are more prominent. Political framework is one of the formative models of the theory of organizational structure. Seyyed Mahdi Shojaee's political satirical novel, Democracy or DemoCrazy depicts the relations between the government and the people in a symbolic region. A reading of the novel in the light of the theory of organizational structure reveals the political structure of the world it depicts, and the laws and ideologies of its different rulers. The present research has an interdisciplinary approach and applies a content analysis method to critique the characteristics of governance in this novel from the perspective of organizational structure in management science. The findings show that the political structure in the novel consists of three main parts: the simple modernist structure, the destructive democratic structure and a seemingly cultured democratic structure. The change of organizational structure in this tripartite system ensures the change of some dimensions of the political structure.